On Cultivating the Courage to Speak Up: The Critical Role of Attendings in the Moral Development of Physicians in Training. (September 2014) - Yerramilli, Divya
Abstract "Shut the door, " the chief resident said to me. While I was green enough at the beginning of my clinical clerkships to believe that most of my medical education would happen at the bedside, at that moment, I was learning another important fact: a large part of my ethical education was going to happen behind the closed doors of a call room. The health care team was polluted by a pervasive atmosphere of frustration, as silent but tangible as a thick layer of fog, that obscured the patient's ability to evaluate the consequences of the choice that lay before her. The attending did not permit, let alone create, an environment that provided room for dissent. Institutions should encourage the leaders of clinical education to foster an emotionally safer learning environment in which honest moral dialogue may occur without fear of repercussions. If students cannot learn to apply the principles of ethics actively throughout their clerkships, it will be much harder to do so when they practice independently, and ultimately, patient care will suffer. Conversely, when students and trainees are empowered by their teachers, patient care improves.